Implementasi Metode Pembelajaran Card Sort Untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Ulum, M Bustanul; Ratnasari, Khurin’in; Zaeni, Akhmad (UAS PRESS, 2024)
This research is motivated by the still low learning motivation among students in schools, particularly in the fifth-grade elementary school level. The researcher focuses on the implementation of the card sorting learning method to enhance student motivation. The aim of this study is to understand the planning, implementation, and evaluation of the card sorting learning model to improve student motivation in this subject area. This is observed through the process of teaching and learning activities, which includes the initial stage of learning, the core learning activities, and the conclusion of the learning process, all aimed at boosting student motivation. This study employs a descriptive qualitative research design. The subjects of this research are fifth-grade students from MI Al-Ma'arif 02 Jombang, as well as the researcher. Data collection techniques used include observation, interviews, and documentation. The findings of this research indicate that: 1) the selection of enjoyable and active learning methods can enhance student motivation, 2) students are enthusiastic about participating in lessons using the card sorting method, 3) students have become more confident and skilled in expressing opinions and actively asking questions, both to peers and to the teacher, and 4) it can help students become more independent and better understand the material presented